2021
DOI: 10.1186/s12943-021-01313-x
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding RNAs regulation of macrophage polarization in cancer

Abstract: Noncoding RNA (ncRNA) transcripts that did not code proteins but regulate their functions were extensively studied for the last two decades and the plethora of discoveries have instigated scientists to investigate their dynamic roles in several diseases especially in cancer. However, there is much more to learn about the role of ncRNAs as drivers of malignant cell evolution in relation to macrophage polarization in the tumor microenvironment. At the initial stage of tumor development, macrophages have an impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(74 citation statements)
references
References 135 publications
1
73
0
Order By: Relevance
“…Previous studies have revealed considerable roles for lncRNAs in the progression and development of human cancers [ 25 , 26 ]. In gastric cancers, a lot of lncRNAs, like CRNDE [ 27 ], RNA1 [ 28 ], have been characterized and their functional mechanism have been reported as well.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed considerable roles for lncRNAs in the progression and development of human cancers [ 25 , 26 ]. In gastric cancers, a lot of lncRNAs, like CRNDE [ 27 ], RNA1 [ 28 ], have been characterized and their functional mechanism have been reported as well.…”
Section: Discussionmentioning
confidence: 99%
“…miRNA class is found in all eukaryotic cells and some viruses. Research in the past few years reported that miRNAs have potential as biomarkers for the early detection and therapeutic targeting of diseases as well as acting as important regulatory elements in healthy and cancerous tissues [48,49]. Of note, miRNAs can be packaged within extracellular vesicles including exosomes and microvesicles, and these vesicles contain numerous miR-NAs that transfer between cells, thereby establishing intercellular communication [50].…”
Section: Mirna Basicsmentioning
confidence: 99%
“…Previous studies have revealed considerable roles for lncRNAs in the progression and development of human cancers 26,27 . In gastric cancers, a lot of lncRNAs, like CRNDE 28 , RNA1 29 , have been characterized and their functional mechanism have been reported as well.…”
Section: Disscussionmentioning
confidence: 99%